Tuning the electrochemical and optical properties of donor-acceptor D-A2-A1-A2-D derivatives with central benzothiadiazole core by changing the A2 strength. (1st February 2021) - Pluczyk-Malek, Sandra; Honisz, Damian; Akkuratov, Alexander; Troshin, Pavel; Lapkowski, Mieczyslaw
Highlights: The novel approach to tuning donor-acceptor benzothiadiazole system was proposed. Two benzothiadiazole derivatives with expanded acceptor part were synthesized. The effect of additional acceptor unit was investigated spectroelectrochemically. The huge impact of structural modification on conjugation level was observed. The effect of acceptor unit on mechanism of electrochemical oxidation was detected. Abstract: Two molecules named QXBT and BXBT with donor-acceptor D-A2 -A1 -A2 -D type of structure were synthesized and characterized by means of electrochemical (Cyclic and Differential Pulse Voltammetry), spectroscopic and spectroelectrochemical (UV–Vis-NIR, Fluorescence and Electron Paramagnetic Resonance) techniques in order to evaluate the impact of different A2 acceptors on properties of such compounds with benzothiadiazole as A1 central core and alkylthiophene donor moieties. In the case of QXBT, the quinoxaline and in the BXBT molecule the benzoxadiazole serves as a A2 unit. The investigations have revealed that changing the A2 allows to tune the conjugation of molecules and affects not only reduction but oxidation process as well. Graphical abstract: Image, graphical abstract